THE THE OTHER PANDEMIC: VIOLATION OF THE SEXUAL FREEDOM OF MINORS IN AN INTRA FAMILY CONTEXT, CRIMINOLOGICAL ANALYSIS FACING THE INCREASE OF CASES DURING THE CONFINEMENT BY COVID-19 - Frank Michael Espinoza Rocha (2021)
The purpose of this work is to analyze from the criminological approach the other pandemic that does not have enough attention and concern on the part of the state and citizens, the violence of sexual freedom against minors in our context of the COVID 19 pandemic, for which we go to statistical, conceptual and doctrinal sources in addition to a critical criminological analysis, which allowed us to first contextualize what was the situation in our country before the pandemic and during the pandemic, analyze the actions of our State through institutions such as the Ministry of the Women and Vulnerable Populations, programs such as the women's help center and the now implemented instruments line 100 and 1801, in order to conclude which are the criminolgical theories of criminal conduct that establish the criminological factors for which this criminal act was presented and why those that increased during confinement.